2019
DOI: 10.1080/24694452.2019.1654843
|View full text |Cite
|
Sign up to set email alerts
|

Please Enter Your Home Location: Geoprivacy Attitudes and Personal Location Masking Strategies of Internet Users

Abstract: Location masking, or geomasking, is a practice typically undertaken by data stewards who wish to release a georeferenced data set without infringing on the privacy of those whose data are involved. With numerous opportunities to transmit our personal locations through electronic devices, individuals have the agency through masking to stem the flow of their location data or otherwise engage in obscuring their locations. Relatively little is known about the factors that influence individuals to protect their loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Therefore, future studies should examine the effect of various geomasking methods on the perceived disclosure risk of maps. Moreover, the perceived disclosure risk measured in the survey may be inflated because people's opinions on locational privacy may be reinforced while conducting the survey (Seidl et al, 2020). Future studies might explore experiments to test alternative sets of wordings of the survey items to optimize results and to test for any bias.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, future studies should examine the effect of various geomasking methods on the perceived disclosure risk of maps. Moreover, the perceived disclosure risk measured in the survey may be inflated because people's opinions on locational privacy may be reinforced while conducting the survey (Seidl et al, 2020). Future studies might explore experiments to test alternative sets of wordings of the survey items to optimize results and to test for any bias.…”
Section: Resultsmentioning
confidence: 99%
“…A considerable literature investigates the reasons why people choose to share their personal location information (Lindqvist, Cranshaw, Wiese, Hong, &, Zimmerman, 2011). While much of this research recognizes that privacy is a concern for most (Kokolakis, 2017; Seidl, Jankowski, Clarke, &, Nara, 2020), they find that for many users the benefits gained from location sharing through services (Budi et al, 2021) or social capital (Ellison, Vitak, Steinfield, Gray, &, Lampe, 2011) outweigh the perceived costs of a loss of privacy. For instance, Alrayes et al (2020) examined the factors contributing to perception of risk to personal privacy associated with sharing location information on social networking applications.…”
Section: Introductionmentioning
confidence: 99%
“…This is another popular area of research, with 66 papers. Some papers (32) focused majorly on this RQ and others (34) reflected on security and privacy behaviors while discussing other concepts such as privacy concerns, awareness, multi-users issues and related conceptual frameworks [4,47,58,61,63,68,70,84,98,100,103,105,114,116,118,123,126,130,134,135,141,144,146,150,164,167,173,178,181,183,187,188,195,200,202]. Here, we will focus on the 32 papers in the former group.…”
Section: Rq5mentioning
confidence: 99%
“…Seidl et al [164]'s study (survey, š‘› = 214) found that geo-privacy behaviors are very much linked to a participant's underlying knowledge of the field and similar across different demographic factors including gender, ethnicity and income level. Huang and Wu [81]'s comparative study on Chinese and US users revealed that users' privacy concerns in China seemed to be lower than in Western countries.…”
Section: Rq5mentioning
confidence: 99%